Case Report: Prolonged survival in Schinzel–Giedion syndrome featuring megaureter and de novo SETBP1 mutation - Beaman, Glenda M.; Jarvis, Benjamin W.; Goyal, Anju; Keene, David J. B.; Cervellione, Max; Lopes, Filipa M.; Metcalfe, Kay A.; Woolf, Adrian S.; Newman, William G. (Frontiers in Pediatrics, 2025)
BackgroundRare early-onset lower urinary tract (REOLUT) disorders affect the ureter, urinary bladder, or urethra and manifest before birth or in childhood. Monogenic causes have been reported in a subset of such individuals.ObjectivesA possible genetic cause was considered in a child with a megaureter who had syndromic features.Subjects and methodsWhole-exome sequencing was undertaken in individuals with megaureter. Immunohistochemistry was performed in urinary tract tissues of unaffected human fetuses.ResultsThe index case presented at 6 months with urosepsis and was found to have a unilateral primary non-refluxing megaureter which required stenting of its distal portion. This, together with dysmorphic features and developmental delay, led to a clinical diagnosis of Schinzel–Giedion syndrome (SGS). She was found to carry a de novo missense variant in SET binding protein 1 (SETBP1), c.2613T>G (GenBank: NM_015559.3) (p.Ile871Met), a gene previously implicated in SGS. She was in good general health at 11 years of age, an unusual outcome given that most individuals with SGS die in the first 2 years of life. SETBP1 was detected in the fetal urinary tract, both in the urothelium and in nerve trunks in the kidney hilum and around the ureter. No SETBP1 gene variants were detected in eight further cases of megaureter.ConclusionsThis case indicates the value of genetic testing when a REOLUT disorder is accompanied by syndromic signs outside the urinary tract. SETBP1 may drive the functional differentiation of the human fetal ureter.